An Optimal Capacity Planning Model for General Cargo Seaport - Dundović, Čedomir; Zenzerović, Zdenka (Promet - Traffic&Transportation, 2012)
In this paper the application of the queuing the01y in optimalcapacity planning for general cargo seaport is presented.The seaport as a queuing syslem is defined and tlws, on the basisof the arrival and serviced number of ships in an obsen•edtime unit, the appropriate operating indicators of a port systemare calculated. Using the model of total port costs, the munberof berths and cranes on the berth can be determined wherebythe optimal port system functioning is achieved.